2017
DOI: 10.1176/appi.ajp.2016.16030333
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of Cognitive Deficits in Victimized Children: Implications for Neuroscientists and Clinicians

Abstract: OBJECTIVE Individuals reporting a history of childhood violence victimization have impaired brain function. However, the clinical significance, reproducibility, and causality of these findings are disputed. We directly tested these research gaps. METHOD We tested the association between prospectively-collected measures of childhood violence victimization and cognitive functions in childhood, adolescence, and adulthood among 2,232 members of the UK E-Risk Study and 1,037 members of the New Zealand Dunedin Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
133
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 141 publications
(154 citation statements)
references
References 54 publications
16
133
1
4
Order By: Relevance
“…The possibility of time-varying confounding, that the behaviors and risk factors that are subsequently affected by exposure to childhood adversity may also increase the risk of adversity, is a major threat to causal inference. For example, findings in a genetically informative British cohort indicated that child characteristics such as intelligence quotient and adjustment problems predicted exposure to maltreatment by adults 140 and chronic peer victimization (bullying). 141 Others have shown the adverse effects of maltreatment and peer victimization on child adjustment.…”
Section: Application Of Modern Epidemiological Methodsmentioning
confidence: 99%
“…The possibility of time-varying confounding, that the behaviors and risk factors that are subsequently affected by exposure to childhood adversity may also increase the risk of adversity, is a major threat to causal inference. For example, findings in a genetically informative British cohort indicated that child characteristics such as intelligence quotient and adjustment problems predicted exposure to maltreatment by adults 140 and chronic peer victimization (bullying). 141 Others have shown the adverse effects of maltreatment and peer victimization on child adjustment.…”
Section: Application Of Modern Epidemiological Methodsmentioning
confidence: 99%
“…Childhood and adolescent victimization experiences in this cohort have been described previously (2, 25) and are summarized here (details are provided in the online data supplement). …”
Section: Methodsmentioning
confidence: 99%
“…Early-life stress is thought to cause many adverse health outcomes, including altered brain development (1), compromised cognitive functioning (2), poor mental health (3), and multiple physical illnesses (4). Perhaps the most pressing question at the nexus of neurobiology and public health is how stress “gets under the skin” to bring about these pleiotropic effects (59).…”
mentioning
confidence: 99%
“…This test is necessary because inconsistencies between animal and human research may arise for several reasons, including differences in life history and brain development timing across species, greater individual differences in human versus animal studies, or routine compensatory interventions (e.g. schooling, child protection services) in human studies (Clancy, Finlay, Darlington, & Anand, ; Danese et al, ; van der Worp et al, ).…”
Section: How?mentioning
confidence: 99%